2014
DOI: 10.1007/s11842-014-9262-x
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Forestry Extension Encounters: A Conversation Analysis Approach

Abstract: This article assesses cooperative features of forestry advising encounters with an emphasis on their pedagogical positioning. The study argues that only an in-depth analysis can reveal the multifaceted nature of the advisory interaction and provide systematic justifications for extension service enhancement. Authentic video recordings of advisory encounters between a forestry extension advisor (FEA) and family forest owners (FFOs) are scrutinized using the qualitative approach of conversation analysis and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Finding a balance between face-to-face advising and internet-mediated decision support services is important. Advising FOs in person potentially constructs shared knowledge and promotes learning (Virkkula and Hujala 2014). Successful advising generates trust and respect between FO and forest professional and strengthens one's conception of themselves as forest owner (Hujala and Tikkanen 2008), which may help estranged or less interested forest owners to take initiative about their forests.…”
Section: Need For User-oriented Decision Support Services Is Evidentmentioning
confidence: 99%
“…Finding a balance between face-to-face advising and internet-mediated decision support services is important. Advising FOs in person potentially constructs shared knowledge and promotes learning (Virkkula and Hujala 2014). Successful advising generates trust and respect between FO and forest professional and strengthens one's conception of themselves as forest owner (Hujala and Tikkanen 2008), which may help estranged or less interested forest owners to take initiative about their forests.…”
Section: Need For User-oriented Decision Support Services Is Evidentmentioning
confidence: 99%
“…The traditional linear form focuses on the delivery and receipt of knowledge between a forestry professional and forest owner although this interaction can be complex. In analysing such interactions, Virkkula and Hujala (2014) found that the delivery and receipt of information generally followed the linear form but that owners would typically engage and guide the conversation if they desired. Kuhns et al (1998) showed that forest owners expressed a preference for personal contact with knowledge transfer professionals.…”
Section: Introductionmentioning
confidence: 99%
“…These landowner communication channels and social network structures are just now being explored in the literature. The results of many studies demonstrate where landowners prefer to receive information, how they use the information they receive, who they interact with, and how much they trust information and individuals with whom they interact [ 6 , 7 ]. Of particular importance is the role of influential acquaintances or peer leaders in communities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these landowners may also receive information from written sources such as websites, newsletters, e-mail listserves, and scientific literature [ 28 ]. Unsurprisingly, landowners seem to prefer face-to-face interactions for information [ 7 ], but judge interactions less by scientific credibility or professional expertise and more on social impressions [ 29 ]. Often, landowners prefer a combination of practical advice from peers and technical information from professionals [ 30 ].…”
Section: Introductionmentioning
confidence: 99%